1998
DOI: 10.1093/humrep/13.10.2688
|View full text |Cite
|
Sign up to set email alerts
|

A comparative prospective study of a chronic low dose versus a conventional ovulation stimulation regimen using recombinant human follicle stimulating hormone in anovulatory infertile women

Abstract: The efficacy and safety of a chronic low dose (group A) and a conventional (group B) stimulation regimen of recombinant human follicle stimulating hormone (r-HFSH) were compared in 103 WHO Group II infertile women with clomiphene citrate-resistant anovulation. Mono- or bifollicular development was induced in 88.1% of patients in group A compared with 76.1% in group B. Ovulation and pregnancy rates were higher in group A (71.4% and 33.3%, respectively) than in group B (63.0% and 20%), but these differences were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 0 publications
1
11
0
2
Order By: Relevance
“…Various studies suggest four parameters of FSH administration management involved in the risk of multifollicular development: (a) the choice of the FSH starting dose,[3435](b) the duration of the starting, dose before stepping up or stepping down,[3436](c) the rate of increase in FSH dose at each increment[37] and (d) the reduction of the FSH dose once a follicle has been selected. [38]…”
Section: Role Of Lh In Physiology: the Physiological Hormonal Interplaymentioning
confidence: 99%
“…Various studies suggest four parameters of FSH administration management involved in the risk of multifollicular development: (a) the choice of the FSH starting dose,[3435](b) the duration of the starting, dose before stepping up or stepping down,[3436](c) the rate of increase in FSH dose at each increment[37] and (d) the reduction of the FSH dose once a follicle has been selected. [38]…”
Section: Role Of Lh In Physiology: the Physiological Hormonal Interplaymentioning
confidence: 99%
“…Indeed, numerous studies have shown that the method of stimulation (chronic low dose, step up, or step down) carries far more weight as a risk factor than the type of injectable gonadotropin used (50,51). Specifi cally, the so-called chronic low dose regimen is more likely to result et al (46) compared 119 cycles of rFSH (Gonal-F) to 114 cycles of highly purifi ed urinary FSH (uFSH-HP) (Metrodin HP).…”
Section: Severe Ovarian Hyperstimulation Syndrome 345mentioning
confidence: 99%
“…On a obtenu une ovulation monofolliculaire dans 74 % des cycles chronic low dose contre 27 % dans les cycles standards et le nombre de follicules supérieurs à 16 mm de diamètre comme les taux d'estradiol étaient de moitié inférieurs dans ce premier protocole. Une grande étude multicentrique française [241] a comparé un protocole conventionnel avec le protocole chronic low dose chez 103 patientes anovulatoires du groupe II de l'OMS. L'emploi de faibles doses s'est soldé par un taux de grossesse supérieur (33,3 contre 20 %) avec moins de grossesses multiples (14 contre 22 %).…”
Section: Traitement Par Gonadotrophinesunclassified